Kardiochirurgia dorosłychEffects of ischemic heart disease operations with use of Cardiac Pulmonary Bypass (CPB) and without it, using the Off-Pump Coronary Artery Bypass (OPCAB) technique on the chosen subpopulations of lymphocytes: potential usefulness in the routine clinical diagnostics - Wilczek, Piotr; Religa, Zbigniew; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background: The use of less invasive operative techniques, such as OPCAB (off-pump coronary artery bypass), can significantly reduce the inflammatory response, thus decrease the mortality as well as the postoperative complications in patients after the cardiovascular operation. Aim: The objective of this study was to compare the number of selected immunocompetent cells in two groups of patients with ischemic heart disease operated with the usage of cardiac pulmonary bypass and those operated using the OPCAB technique. Mo-reover, a trial was made in order to define the usefulness of examined receptors in routine clinical diagnostics for estimation of postoperative complication risk in the investigated groups. Material and methods: Patients were divided into two groups: A – those operated using CPB, B – those operated using OPCAB. Blood for the investigation was taken from patients at the following time intervals: before heparin administration, and next samples were taken 5, 15, 30, 60, 120 and 240 minutes after the start of the surgical procedure. The CD4, CD8, CD3, CD16, CD19 and CD25 receptors were investigated. Results: The most significant differences between two groups of patients were observed for the cells expressing CD16, CD19 and CD25 receptors. In the OPCAB group, the CD16 cells increase significantly 60 min after the start of the surgical procedure and decrease below the control value in the 240th minute. Our study shows also a decrease in CD3, CD4 and CD8 receptors in the CPB group. The CD19 positive cells decrease significantly in the CPB group during the surgical procedure, back to the control value 240 min after the start of the procedure. The CD25 positive cells increase significantly in the CPB group. No significant differences for the investigated receptors were observed in the OPCAB group. Conclusion: It seems that the examination of the selected immunocompetent cells can be useful in the routine clinical diagnostics. CPB, as compared to the OPCAB technique, seems to cause major suppression of immunological response which can make the patients more susceptible to infections. However, it should be noticed that in the OPCAB group, the primary number of cells positive to a given receptor is lower than in patients operated with the usage of CPB. Therefore, it could turn out that the risk of postoperative com-plications is similar in both groups of patients.